IV. Congress on burns, fire disasters and sympossium on plastic surgery : September 18.-20., 1995, Košice - Slovakia : programme and abstracts (Pressko, 1995)
A collection of abstracts of papers presented at a sympossium that focused on burn medicine, disaster medicine and plastic surgery. Intended for professional public.
Keywords: požáry; Congresses as Topic; Fires; kongresy jako téma; plastická chirurgie; Burns; Plastic Surgery Procedures; popálení; Disaster Planning; plánování postupu v případě katastrof; popáleninová medicína; urgentní lékařství; zákroky plastické chirurgie